(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The Behavior Analysis (BA) has benefited in the past and continues to benefit from a specific kind of operational interpretations of terms/expressions developed in other systems of Psychology and similar areas. The Skinnerian model of the operational interpretation of terms of other theories consists of the analysis of the context where theoreticians and researchers emit the analyzed terms/expressions. Therefore, these interpretations are analysis of the verbal behavior of psychologists. Innumerable examples of this practice can be found in the workmanship of Skinner and are recurrent in diverse periodics of the BA. In this article we argue the implications of these analyses for the survival of the BA as a cultural practice, for the conceptual, theoretical, and technological perfectioning of the BA and for teaching BA. Based on these analyses, it can be argued that the interpretation of terms of other theories should be considered an important program of research and should receive greater attention from the behavior analysts.